The Impacts of Energy Consumption by Sector and Foreign Direct Investment on CO2 Emissions in Malaysia - Mohd Shahidan, Shaari; Wen, Chiat Lee; Abdul Rahim, Ridzuan; Evan, Lau; Faiz, Masnan (MDPI, 2022)
The global push for sustainable development has brought environmental issues to the fore. As minimizing environmental deterioration implies reducing energy consumption, this has come under intense discussion among economists and policymakers. This is because it may affect productivity, and thus slow economic growth ensues. Most earlier studies focused on overall energy consumption rather than energy use by sector to see how it can affect CO2 emissions. However, little research has been conducted on the connection between energy use in particular sectors, such as agriculture and transportation, and CO2 emissions. Therefore, this study aims to investigate the impacts of energy use in Malaysia’s transportation, industrial, and agricultural sectors and foreign direct investment (FDI) on CO2 emissions between 1989 and 2019. The ARDL technique is employed, and the results demonstrate that energy consumption in the transportation sector has a greater impact on CO2 emissions than in the industrial sector. On the other hand, energy use in the agricultural sector reduces CO2 emissions. These findings may help policymakers formulate the right policies in specific sectors to benefit communities. They will be at low risk of suffering from diseases attributed to environmental degradation.